Doping v športu in terapevtske izjeme - Osredkar, Joško (Šport (Ljubljana), 2020)
For quite some time, the importance of participating has become of little relevance in elite sport, as it now only applies to recreational sport. Many athletes, and also the sport experts who work with them, have been seeking answers to the question of how to achieve top result by means of training and purely committed way of living. However, some athletes and/or their support staff wish to further improve their physical abilities by consuming prohibited substances and applying prohibited methods that feature on the List of Prohibited Substances and Methods ("the Prohibited List"), published annually by the World Anti-Doping Agency (WADA) which was established at the end of the 1990s to internationally coordinate the fight against doping (World Anti-Doping Agency, 2020). There are athletes who simply could not train and compete without using specific substances from the Prohibited List because of a specific disease (Therapeutic Use Exemptions, 2020). Athletes can suffer from diseases or conditions that require from them to take specific medicines. These athletes are allowed to take such medicine for therapeutic purposes. The aim of the international standard for therapeutic use exemptions is to ensure that the therapeutic exemption allocation procedure is aligned by sport and by country.
Keywords: doping; prepovedane snovi; prepovedani postopki; prohibited methods; prohibited substances; šport; terapevtska uporaba; therapeutic use